Extracellular matrix influence in Streptococcus mutans gene expression in a cariogenic biofilm - Florez Salamanca, E. J. [UNESP]; Klein, M. I. [UNESP] (Wiley, 2018)
Caries etiology is biofilm–diet-dependent. Biofilms are highly dynamic and structured microbial communities enmeshed in a three-dimensional extracellular matrix. The study evaluated the expression dynamics of Streptococcus mutans genes associated with exopolysaccharides (EPS) (gtfBCD, gbpB, dexA), lipoteichoic acids (LTA) (dltABCD, SMU_775c) and extracellular DNA (eDNA) (lytST, lrgAB, ccpA) during matrix development within a mixed-species biofilm of S. mutans, Actinomyces naeslundii and Streptococcus gordonii. Mixed-species biofilms using S. mutans strains UA159 or ΔgtfB formed on saliva-coated hydroxyapatite discs were submitted to a nutritional challenge (providing an abundance of sucrose and starch). Biofilms were removed at eight developmental stages for gene expression analysis by quantitative polymerase chain reaction. The pH of spent culture media remained acidic throughout the experimental periods, being lower after sucrose and starch exposure. All genes were expressed at all biofilm developmental phases. EPS- and LTA-associated genes had a similar expression profile for both biofilms, presenting lower levels of expression at 67, 91 and 115 hours and a peak of expression at 55 hours, but having distinct expression magnitudes, with lower values for ΔgtfB (eg, fold-difference of ~382 for gtfC and ~16 for dltB at 43 hours). The eDNA-associated genes presented different dynamics of expression between both strains. In UA159 biofilms lrgA and lrgB genes were highly expressed at 29 hours (which were ~13 and ~5.4 times vs ΔgtfB, respectively), whereas in ΔgtfB biofilms an inverse relationship between lytS and lrgA and lrgB expression was detected. Therefore, the deletion of gtfB influences dynamics and magnitude of expression of genes associated with matrix main components.
Keywords: exopolysaccharides; extracellular DNA; lipoteichoic acids; starch; sucrose